Knowledge Sharing in Knowledge-based Institutions - Jessica Sze-Yin, Ho; Cheng Ming, Yu; Lau Pei, Mey (2008)
Recent development has witnessed the emergence of new economy where knowledge has become a valuable resource and asset. As things change speedily in this new economy, fire concern is not only on how much you know, but also how quickly you can capture and apply what you have learnt. fit many ways, knowledge sharing is envisaged as a natural activity of academic institutions. Tire number of seminars, conferences and publications by academics is far exceeding any other profession, signifying the eagerness and generosity of academics to share knowledge. However, a closer look tit the problem might reveal a different story; instead of knowledge sharing, "knowledge hoarding" could be more prevalent in academic institutions. This paper examines the knowledge sharing behaviour among academics. The overall findings revealed that incentive system and personal expectation are two key factors in driving academics to engage in knowledge sharing activity